Rejuvenation : From the East; Japan-Korea 1990 : [Seoul-Tokyo-New York] Art Project. - Minamishima, Hiroshi; Sagacho Exhibit Space, Tokyo (Tokyo : [Seoul-Tokyo-New York] Art Project, 1990)
Ikeda, Ichi ; Ishihara, Tomoaki ; Tonoshiki, Tadashi ; Miyajima, Tatsuo ; Lee, Kun-Yong ; Park, Eun-Soo ; Pang, Hyo-Sung ; Yook, Geon-Byung
This catalog is an account of the exhibit "Eight Individuals from EAST", at the Sagacho Exhibit Space and the accompanying symposium "Art-Orientation" held at the Heineken Village Gallery, Tokyo, 1990.03 - 30.4.27
kunstcatalogus